Immature stages of Pleuronota rufosquamosa (Fairmaire, 1893) (Coleoptera: Scarabaeidae: Cetoniinae), with notes on its biology - Wen, Hui; Zhang, Xin-Yuan; Qiu, Jian-Yue (Zootaxa, 2024)
Pleuronota rufosquamosa (Fairmaire, 1893) is a little-known flower beetle from southern China and northern Vietnam, and due to taxonomic changes, the genus Pleuronota Kraatz, 1892 and the species became new records of China. Morphological characteristics of adults are redescribed. Descriptions of the 3rd instar larvae and pupae are also provided, and the morphological differences of the larvae are compared with four genera of the subtribe Taenioderina. All morphological structures are supplemented by photographs. The life history of P. rufosquamosa is briefly summarized based on field observation and artificial breeding.